2015
DOI: 10.1021/acs.jnatprod.5b00481
|View full text |Cite
|
Sign up to set email alerts
|

Cafestol, a Bioactive Substance in Coffee, Stimulates Insulin Secretion and Increases Glucose Uptake in Muscle Cells: Studies in Vitro

Abstract: Diet and exercise intervention can delay or prevent development of type-2-diabetes (T2D), and high habitual coffee consumption is associated with reduced risk of developing T2D. This study aimed to test whether selected bioactive substances in coffee acutely and/or chronically increase insulin secretion from β-cells and improve insulin sensitivity in skeletal muscle cells. Insulin secretion from INS-1E rat insulinoma cells was measured after acute (1-h) and long-term (72-h) incubation with bioactive substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 32 publications
4
46
0
1
Order By: Relevance
“…The beneficial, but moderate effect of caffeic acid on acute insulin secretion reported by (Mellbye et al, 2015) was consistent with the findings of Bhattachaya et al 2014, who also showed that chronic exposure to the phenolic acid further enhanced the secretory response from INS1E beta cells. This effect was maintained following chronic treatment with high glucose concentrations, suggesting a protective effect of the compound on beta cell survival when exposed to stressful conditions typical of type 2 diabetes.…”
Section: Coffee Compounds and Insulin Secretionsupporting
confidence: 88%
See 2 more Smart Citations
“…The beneficial, but moderate effect of caffeic acid on acute insulin secretion reported by (Mellbye et al, 2015) was consistent with the findings of Bhattachaya et al 2014, who also showed that chronic exposure to the phenolic acid further enhanced the secretory response from INS1E beta cells. This effect was maintained following chronic treatment with high glucose concentrations, suggesting a protective effect of the compound on beta cell survival when exposed to stressful conditions typical of type 2 diabetes.…”
Section: Coffee Compounds and Insulin Secretionsupporting
confidence: 88%
“…More significant changes regarding glucose uptake were observed in a liver cell line (Huang, Shen, & Wu, 2009). In addition Mellbye et al reported of clear beneficial effects on glucose uptake in a muscle cells by another coffee component, cafestol (Mellbye, Jeppesen, Hermansen, & Gregersen, 2015).…”
Section: Impact Of Bioactive Coffee Components On Insulin Resistance mentioning
confidence: 91%
See 1 more Smart Citation
“…Not only does cafestol stimulate the secretion of insulin, but it also improves insulin sensitivity, increasing the uptake of glucose in muscle cells. [33]…”
Section: Discussionmentioning
confidence: 99%
“…Cafestol, stevioside, and isosteviol are diterpenes that increase insulin sensitivity and secretion by modifying the expression of genes and transcriptional factors of insulin regulation, and increasing glucose uptake [75][76][77].…”
Section: Terpenesmentioning
confidence: 99%